Peran serta masyarakat mereduksi sampah anorganik melalui Bank Sampah di Distrik Malaimsimsa Kota Sorong - Andreas Adii; Marlyn N. Lekitoo; Meike M. Lisangan (Program Pascasarjana Universitas Papua, 2022)
The production of household waste increases every day in line with the increase in the number of products and the comsumption pattern of people. The things that must be done to overcome the increase in the amount of waste is by reducing the amount of waste from its source using waste. This study aims to determine the role of the community in the management of inorganic waste through the Waste Bank in the Malaimsimsa District and how much is the contribution of the Waste Bank in reducing the amount of inorganic waste in the Malaimsimsa District and the income that can be obtained through the Waste Bank. This study used a qualitative description method. The results of this study indicate that the existence of a Waste Bank in Malaimsimsa District can reduce waste production in the final dumpsite, but waste recycling and sorting have not been maximally carried out by the community and Waste Bank managers. The composition of the wastes in Malaimsimsa District consists of 39.90% inorganic waste that consist of 29.11% of plastics, 8.8% of papers, 0.17% of glasses/bottles, and 1.82% of iron/can.